KEMAMPUAN TRANSLASI DAN TRANSFORMASI REPRESENTASI MATEMATIS SISWA DALAM OPERASI BILANGAN PECAHAN SEDERHANA - Toha, Mohamad; Bistari, Bistari; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the translation ability and transformation of mathematical representation of students in the operation of simple fractions in class VII MTs IKA - PGA Baiturrahmah Pontianak. The method used in this research is descriptive method. Researchers sought to describe the translation ability and transformation of mathematical representation of students in the operation of simple fractions. The result is the students ability is still very low . The average score representation translation R-V is 1,83. The average score representation translation V-R is 0,5. The average score representation translation V-S is 0,67. The average score representation translation S-V was 1,11. The average score representation translation R-S is 1. The average score representations translation of S-R was 0,36. While the average score transformation capabilities representation R is 1,67, representation V is 1,44 and the representation of S is 2,06.Keywords: Translation, Transformation, Mathematical Representations